KEPEMIMPINAN DIGITAL DAN INOVASI WIRAUSAHA: BUKTI DARI USAHA KECIL DAN MENENGAH - Mukhairir Fikri Ihsan; Devi Susanti (GREET, 2026)
The accelerating pace of digital transformation has repositioned leadership as a critical determinant of entrepreneurial innovation, particularly within resource-constrained small and medium enterprises (SMEs). This study examines how digital leadership shapes entrepreneurial innovation by integrating strategic vision, digital capability, and innovation-oriented organizational culture. Employing a mixed-methods design, this research combines semi-structured interviews with SME leaders and a survey of 300 SMEs across retail, manufacturing, and service sectors. The findings reveal that digital leadership exerts a strong and positive influence on entrepreneurial innovation by enhancing organizational agility, knowledge sharing, customer-centric innovation, and resilience under environmental uncertainty. Empirically, SMEs characterized by high digital leadership demonstrate significantly higher innovation outputs, faster time-to-market, and superior adaptive performance compared to traditionally led firms. The qualitative evidence further uncovers how digitally oriented leaders orchestrate digital tools, collaborative cultures, and learning mechanisms to overcome structural constraints typical of SMEs. This study advances the literature by moving beyond a unidimensional view of digital leadership and empirically demonstrating its integrative role as a strategic capability that links digital transformation, innovation processes, and entrepreneurial outcomes. Practically, the findings offer actionable insights for SME owners, policymakers, and support institutions to embed digital leadership development within entrepreneurship and digitalization frameworks, thereby strengthening SME competitiveness and sustainability in the digital economy.